Selective distributed optical fiber sensing system based on silicone cladding optical fiber and Rayleigh backscattering reflectometry for the detection of hydrocarbon leakages. (June 2023) - Baggio, Andrea; Turani, Matteo; Olivero, Massimo; Salvo, Milena; Pugliese, Diego; Sangermano, Marco
Abstract: A new system that exploits optical fiber distributed sensing for the detection of hydrocarbons is presented. The system relies on a custom-designed silica core/thin silicone cladding optical fiber to provide a quick and selective absorption of oil products through the cladding; moreover, it exhibits insensitivity to water. Optical fiber sensor interrogation is performed by detecting Rayleigh backscattering using an optical time domain reflectometer or, in a high-resolution version, an optical frequency domain reflectometer. The Rayleigh backscattering signal is influenced by a change in the refractive index of the cladding, which locally modifies the guiding properties of the fiber; and by the swelling of the cladding, resulting from hydrocarbon diffusion, that produces local stress and results in an associated increased reflection. The system has been tested with different solvents and has exhibited selectivity and a rapid response to exposure to high refractive index hydrocarbons, with the sensing fiber yielding a response time of the order of 1 s. The system, in its high-resolution version, is able to accurately locate leakages with an accuracy of 14 cm.